Einstein's Equivalence Principle - Golovkin, BG (Annals of Mathematics and Physics, 2026)
Based on Newton's laws and Mach's principle, formulas were derived for the quantitative interdependence of inertial and gravitational mass on Earth, other planets, and in space, explaining Einstein's equivalence principle. It was shown that gravitational mass depends on the velocity of a body in the same way as inertial mass.